PENGARUH PENAMBAHAN TEPUNG DAN HASIL PARUTAN BIT MERAH DALAM PEMBUATAN BISKUIT TERHADAP KANDUNGAN GIZI - winda melisa; evawany yunita; jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Beetroot (Beta vulgaris L) is significantly suitable to consider in supporting the food diversification. To support food diversification, need to be introduced products beetroot to get a new food alternatives. Beetroot is potential as a source of nutrients, as well of its macro and micro nutrients contents. One of processed that can be made from beetroot that is biscuit that can be kind of biscuit on the market. This study was the experiment of making biscuit with the addition beetroot flour and grated for 20%. The purpose of this experimental study to know the influence of addition beetroot flour and grated on nutrients composition biscuit. Content of phosphorus, calcium, iron based on the analysis of AAS (Atomic Absorption Spectrophotometry), content of energy, carbohydrate, protein and fat calculation based of DKBM (Lisf of Food Composition). The result of this experiment showed that content of phosphorus, calsium, iron more higher than the biscuit without addition of beetroot. Biscuit beetroot flour have content of phosphorus 129,73 mg, calsium 91,26 mg, iron 3,95 mg, meanwhile biscuit beetroot grated have content of phosphorus 91,53 mg, calsium 65,81 mg, iron 3,11 mg. Based on calculation of DKBM (List of Food Composition), showed that the biscuit beetroot flour has highest content of energy, carbohydrate,  fat, meanwhile the biscuit beetroot grated only content of fat that high. It’s recommended for people to take beetroot biscuit as alternative food. Also, it is necessary to research to use beetroot for other foods diversification. Keywords: biscuit, beetroot, nutrient composition.